Etika Bisnis Islam pada Implementasi Tanggung Jawab Sosial Perusahaan - Rahmawati, Indriyani Dwi; Jubaedah, Dedah (Bertuah Jurnal Syariah dan Ekonomi Islam, 2024)
Companies are one of the pillars of economic development and companies cannot stand alone without the support of the community. Profit is not the only goal of the establishment of the company, but the company is also required to create welfare. This article will discuss the application of the principles of Corporate Social Responsibility in the perspective of Islamic business ethics. This study uses a narrative qualitative approach with a literature review method to inform readers of research results that are closely related to the topic being researched and connect the research topic with existing literature. The data collection technique used is a secondary data collection technique with the data analysis technique used is the Miles and Huberman data analysis and analysis technique, which consists of data collection, data reduction, data presentation, and conclusion drawn. Indonesia's CSR practices have been carried out by several companies in several sectors such as Pertamina in CSR in the economic sector, Bank BRI in CSR in the education sector, Adaro CSR in the environmental sector, BSI University CSR in the social sector, and Huawei Indonesia CSR in the infrastructure sector.